Building Evidence, Shaping Policy : Findings of the 2012 Timor-Leste Education Survey - World Bank (World Bank, Dili, 2016)
Reliable evidence is needed to design policies that will allow overcoming Timor-Leste's remaining challenges in provision of quality education. In recent post-conflict years, aided by availability of oil revenues, Timor-Leste has been able to considerably improve availability of schools and access to education. This report presents findings of the 2012 Education Survey, collaboration between the Ministry of Education, the National Directorate of Statistics, AusAID and the World Bank. The survey collected detailed information at all primary, pre-secondary and secondary schools in the country. Its objectives were to support the improvement of Timor-Leste's education quality and service delivery through building a solid information source and analytical foundation which will allow for sound, evidence-based policy making. The survey results indicate that student absenteeism should be a major cause for concern. More than one third of grade one students were absent from school on the day of the survey, in some districts it was half or even more. Education levels of primary school teachers are low, with the majority only having secondary education. For 71 percent of primary school teachers the highest level of education is secondary school, for 6 percent it is even lower. Both demand and supply side interventions are needed to tackle the challenges faced. Some key policy areas should be: 1) improving school attendance through creating appropriate demand-side incentives; 2) enhancing teacher quality; 3) strengthening instruction language policy; 4) improving education system management; 5) improving school infrastructure and learning environment; and 6) ensuring adequate supply of textbooks.